2018
DOI: 10.1007/s00066-018-1308-0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care analysis for head & neck cancer of unknown primary site: a survey inside the German society of radiation oncology (DEGRO)

Abstract: Diagnostics and treatment for SCCHN CUP within the DEGRO remain heterogeneous. A prospective register trial with standard operation procedures is warranted to homogenize and possibly improve management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…5 Recently, an increasing trend in the epidemiology of SCCUP has been observed. 8 Mounting evidence has shown an increased prevalence of human papillomavirus (HPV)-related SCCUP, which seems to display a better prognosis than non-HPV-related SCCUP, and has a weaker association with tobacco and alcohol abuse. 8 Mounting evidence has shown an increased prevalence of human papillomavirus (HPV)-related SCCUP, which seems to display a better prognosis than non-HPV-related SCCUP, and has a weaker association with tobacco and alcohol abuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recently, an increasing trend in the epidemiology of SCCUP has been observed. 8 Mounting evidence has shown an increased prevalence of human papillomavirus (HPV)-related SCCUP, which seems to display a better prognosis than non-HPV-related SCCUP, and has a weaker association with tobacco and alcohol abuse. 8 Mounting evidence has shown an increased prevalence of human papillomavirus (HPV)-related SCCUP, which seems to display a better prognosis than non-HPV-related SCCUP, and has a weaker association with tobacco and alcohol abuse.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Due to the rarity of SCCUP, the available literature is limited to small retrospective studies using different diagnostic criteria and treatment strategies. 8 Mounting evidence has shown an increased prevalence of human papillomavirus (HPV)-related SCCUP, which seems to display a better prognosis than non-HPV-related SCCUP, and has a weaker association with tobacco and alcohol abuse. 9 The interest toward HPV-related SCCUP has been growing consequent to the refinements in diagnostic procedures and better understanding of the natural history of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…After an intensive literature search in Pubmed and Medline we have only found one comparable survey about patterns of care for CUP. It has been performed recently in Germany, only included radiation oncologists and has revealed that 82% of the departments routinely determined HPV status in CUP (48). This rate is significantly higher than in Switzerland.…”
Section: Results and Discussion Of Biomarkers With Current Potential Usementioning
confidence: 99%
“…der transoralen Laser-Mikrochirurgie hingewiesen. Auf der Basis einer Umfrage unter den Strahlentherapeuten in Deutschland wird die 18 F-FDG-PET/CT zur Primärtumorsuche vorwiegend an universitären Einrichtungen eingesetzt [10].…”
Section: Pet/ct Bei Carcinoma Of Unknown Primary (Cup)unclassified